INFILTRASI DAN PERMEABILITAS PADA TANAH REKLAMASI TAMBANG EMAS - Tambunan, Liskawani; Husain, Jailani; Supit, Joice M.J. (EUGENIA, 2018)
ABSTRACTÂ Infiltration and permeability are soil parameters that can be used to describe the extent of land damage caused by the mining process. In accordance with Law No. 4.of 2009 on Mineral and Coal Mining, that reclaiming mining land is obligatory for every company that manages it. This study aims to determine the rate of infiltration and permeability on the reclaimed gold mined land. The research was conducted at the gold mining location of Bakan and Lanut. Infiltration measurements were carried out on straight line transect along the foot slope to the top slope. Measurements were made at two meter distance in 5 cm depth along the transect line direction using the Guelph Permeameter. Hydraulic conductivity was calculated from infiltration data. This research revealed that reclamation has positive effect in increasing of infiltration rate and permeability. Crop dan root growth should have contributed in increasing soil organic matter, root and microbial activities, which leads to improve soil texture and soil structure.Keywords: infiltration, permeability, reclaimed